A Study of Employability Soft Skills of Final-Year Students: A Case of Gedu College of Business Studies - Loday, Sonam; Drakpa, Dawa (Technium Social Sciences Journal, 2021)
Employability soft skills is a set of highly desirable, transferable skills that turn one into an attractive employee. It can be defined as a set of skills employers want from a potential employee. This study was designed to evaluate the employability soft skills of Gedu College of Business Studies’ Students and for evaluation, the quantitative research design was adopted. A proportionate sampling method was used and enumerated 228 B. Com and BBA students. Collected data were analyzed using a one-sample t-test and an independent sample t-test. The result reveals that Gedu College of Business Studies’ students possess above-average employability soft skills where the mean score is greater than the test value (3). It further reveals that there is no statistically significant mean difference in employability soft skills between male and female students apart from problem-solving skills which were found statistically significant (p=.046, p<0.05).